Optimization Technology of Frequency Conversion Constant Pressure Control System of Mine Emulsion Pump Station in Electrical Engineering and Automation Specialty - Cong Tian; Xiwen Wei; Chao Yang; Chang Su (Advances in Civil Engineering)
No matter in metal mines or coal mines, an emulsion pump station has a wide range of application market and can play an important role. In this paper, the frequency conversion constant pressure control system of the mine emulsion pump station is taken as the research object. The two kinds of water-based drawing fluids used are dispersed drawing fluid and emulsion drawing fluid. After the intelligent level of the equipment reaches a very high level, an environmentally friendly, safe, and efficient Internet of Things technology system will be added. Combined with 3D laser scanning technology based on self-scanning of road contours, the blast method is input to the terminals of the emulsion pump station for automatic blast hole positioning and semiautomation of the emulsion pump station. Combined with 5 g communication and other intelligent key technologies, it realizes high-end functions such as fault self-diagnosis, remote operation, and remote monitoring of the emulsion pump station and rock drill, which can be called full intelligent stage. The results show that the initial friction coefficient of drawing fluid A lubrication is 0.21, and then, with the extension of time, the friction coefficient gradually decreases to 0.14. The initial friction coefficient of drawing fluid B is 0.22, then it decreases rapidly to 0.13, then it is stable at 0.17, and then it remains basically unchanged. When the temperature is 55°C, the initial friction coefficient is 0.16 and then decreases to 0.12. Therefore, the frequency conversion constant pressure control system of the mine emulsion pump station should be selected according to the environment and application scenarios.